Tinjauan Kelengkapan Pengisian Formulir Persetujuan Tindakan Kedokteran Pasien Bedah Rawat Inap Di Rumah Sakit Tere Margareth Tahun 2022 - Sabela Hasibuan, Ali; Ritonga, Zulham Andi; Simanjuntak, Marta; Nababan, Edward Ramos (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Completeness of filling in the informed consent form is very important because it can affect the quality of medical records and the legal aspects contained in the medical records themselves. This type of research is descriptive with an observational approach, namely research that describes the current situation. The study population was the medical record document of the informed consent form of inpatients with the sample in this study being a portion of the total population. An overview of the completeness of filling out informed consent sheets in surgical cases at Tere Margareth General Hospital can be seen from the sample count with a total population of (235) divided by 1+235 (precision level/10%=0.1) which results in a sample of 70. Completeness of filling in the identification of providing information is 97% filled and 3% not filled. Completeness of filling in important report items is 92% filled and 8% not filled. Completeness of filling in medical action items is 98% filled and 2% not filled. Completeness of filling in authentication items is 87% filled and 3% not filled. The medical record unit is trying to be able to ask the nurse in charge to fill out the informed consent form so that it can fill it out completely.